2008
DOI: 10.1080/10888700802329939
|View full text |Cite
|
Sign up to set email alerts
|

Feeder Use Patterns in Group-Housed Pregnant Sows Fed With an Unprotected Electronic Sow Feeder (Fitmix)

Abstract: Previous studies on feeder use in group-housed pregnant sows focused on dynamic groups and protected electronic sow feeders (ESF). This study observed 60 pregnant sows, 1st to 8th parity--housed from Day 29 of pregnancy to 1 week before parturition in stable groups of 20 animals, 1 Fitmix feeder per group. Data from 25 nonconsecutive 24-hr feeding cycles showed sows making several visits to the feeder. Literature on conventional ESF indicated shorter daily feeder occupation. Daily feeder occupation per sow dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Feed order ranking of ESF systems has previously been shown to be fairly stable and correlated to social dominance; with more aggressive and older sows eating earlier than other sows (Hunter et al, 1988;Chapinal et al, 2008). The positive correlation between feed rank at 2 to 4 weeks of gestation and aggressive/dominant scores indicates that sows which displaced others more often, and initiated more aggressive behaviors, also ate their daily feed earlier than other sows.…”
Section: Personality Traits In Gestating Sowsmentioning
confidence: 83%
See 1 more Smart Citation
“…Feed order ranking of ESF systems has previously been shown to be fairly stable and correlated to social dominance; with more aggressive and older sows eating earlier than other sows (Hunter et al, 1988;Chapinal et al, 2008). The positive correlation between feed rank at 2 to 4 weeks of gestation and aggressive/dominant scores indicates that sows which displaced others more often, and initiated more aggressive behaviors, also ate their daily feed earlier than other sows.…”
Section: Personality Traits In Gestating Sowsmentioning
confidence: 83%
“…Typically a small number of sows (6 to 10) are waiting at the feeder entrance and competing for access the feed station. Given that feed order is relatively stable (Hunter et al, 1988;Chapinal et al, 2008) sows are familiar with their waiting partners and likely have an implicit hierarchy in place. Once inside the electronic feeder the sows eat alone and thus this feeding system is characterized as noncompetitive feeding (Bench et al, 2013).…”
Section: Personality Traits In Gestating Sowsmentioning
confidence: 99%
“…Feeding rates and other behavior information may be valuable tools in pig production. According to the literature, feederuse patterns in grouphoused pigs may be affected by several factors, such as photope riodicity, group size, social interaction, management, feed allowance, equipment design, and the type of en vironment in which feeder use is observed (Nielsen, 1999;Chapinal et al, 2008). Some feedback systems related to nutrient intake and based on internal meta bolic balances may also influence feeding behavior, es pecially in terms of shortterm regulation.…”
Section: Resultsmentioning
confidence: 99%
“…A better understanding of pig feeding behav ior could provide critical information for improving feeding strategies, productivity, and animal wellbe ing. Electronic feeders may be an important tool in this research area, as this equipment allows recording detailed and quantitative information on feeding be havior (such as time, size, and duration of each meal), overcoming the lack of control over individual behav ior intrinsic to other grouphousing systems (Nielsen, 1999;Chapinal et al, 2008). The aim of the present study was therefore to conduct an exploratory study of the feeding behavior of group-housed growing-finish ing pigs reared under precision feeding strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Each study included combinations of parameters of feed intake, feeding time, feeding interval, number of feeds per day, total time spent on eating and feeding speed. The researchers found that feed intake and feeding behavior was impacted by environmental temperature (Eigenberg et al, 2000), diet (Fuller et al, 1995;Abijaoudé et al, 2000), social communication (Goetsch et al, 2010), dominance ranking (Chapinal et al, 2008;Val-Laillet et al, 2008;Walker et al, 2008;Soł-tysiak and Nogalski, 2010), number of individuals in a feeder (Korthals, 2000) and health status (Griffin, 2001). However, most of these data were recorded from small groups or individually housed animals.…”
Section: Introductionmentioning
confidence: 99%